Comparative Impact of Double Purse-String Versus Single-Layer Continuous Uterine Sutures in Cesarean Section Outcomes: A Prospective Randomized Controlled Trial - Sheimaa Mohsen MOHAMMAD (Modern Medicine)
Background: Uterine closure techniques affect cesarean section (CS) outcomes. A single-layer continuous suture is simple, but it could rupture the uterus during subsequent pregnancies. The double purse-string suture aims to improve scar quality and myometrial thickness. Objective: The prospective randomized controlled trial investigated the outcomes associated with double purse-string versus single-layer continuous uterine sutures on residual myometrial thickness (RMT), scar width, and healing ratio following cesarean delivery. Subjects and Methods: A total of 149 pregnant women were recruited at the Maternity and Children Hospital in Diwaniyah City, Iraq, at the time of their cesarean delivery. Patients were randomly assigned into two groups: 92 patients to the double purse-string suture group and 57 patients to the single-layer continuous suture group. All cesarean deliveries were performed by proficient obstetric surgeons following standardized surgical procedures for abdominal and uterine incisions. The impact of suturing techniques on the outcomes of CS was assessed by measuring RMT, scar width, and healing of the uterine wall six weeks postoperatively with the use of transvaginal ultrasound. Secondary outcomes included measuring intraoperative blood loss and operation time. Results: The double purse-string suture group had significantly lower blood loss (262.39 ± 76.16 mL) compared to the single-layer group (410.37 ± 116.0 mL, p<0.001). RMT was greater (10.05 ± 1.39 mm vs. 5.70 ± 1.39 mm, p<0.001), and scar width was narrower (37.48 ± 1.73 mm vs. 44.67 ± 3.39 mm, p<0.001). Operation time was longer (17.71 ± 1.74 minutes vs. 14.84 ± 1.85 minutes, p<0.001), and healing ratio was lower (12.0% vs. 36.8% complete healing, p<0.001). Findings from regression analysis showed that the double pursestring suture was positively associated with greater RMT (β=0.84, p<0.001) and negatively associated with scar width (β=−0.82, p<0.001). Logistic regression showed that double purse-string suture was significantly associated with delayed healing (OR = 0.23, p= 0.001). Conclusion: The results suggest that the double purse-string suture offers significant advantages in reducing blood loss and enhancing RMT and scar width, albeit with the trade-off of increased operation time and delayed healing.